Structural interpretation and structural modelling of carbonate and clastic reservoir analogue, Løvehovden, northern Billefjord, Svalbard - Bonet Ruiz, Gerard (The University of Bergen, 2009)
The Master's Thesis is centred in the topics of structural geology and structural modelling. I present a reinterpretation of the Løvehovden reverse Tertiary faults from Dallmann et al. (2004) as syn-depositional Carboniferous extensional faults based on sedimentological and structural evidence. The structural models are intended to quantify basin thickness variations, compaction, flexural isostatic rebound and Tertiary shortening. Trishear models are tested in order to assess the Løvehovden Master Fault propagation, trishear apex and trishear angle of the fault-propagation fold observed in the Løvehovden study area. The stratigraphic sequence deposited in the study area forms a petroleum system, where the effects of compaction on fluid migration and analogy with the Barents Shelf are here evaluated. Petroleum potential of the study area is particularly discussed in the Appendix. Master i Geovitenskap - Petroleumsgeofag MAMN-GVPET GEOVPETR